Surface Microstructure Regulation of Porous Polymer Microspheres by Volume Contraction of Phase Separation Process in Traditional Suspension Polymerization System. Issue 17 (12th March 2019) - Wang, Jiqi; Yang, Zuoting; Xu, Jia; Ahmad, Mudasir; Zhang, Hepeng; Zhang, Aibo; Zhang, Qiuyu; Kou, Xiaokang; Zhang, Baoliang
Abstract: In the present work, the suspension polymerization method is used for the preparation of porous polymer microspheres with different surface morphology, and the preparation mechanism is systematically expounded. The morphology results show that the smooth, convex, and wrinkled microspheres could be controlled by adjusting the ratio of monomer to porogens. The micelles forming the framework support the "Eggshell, " and its size and shape directly affect the morphology of "Eggshell." The addition of monomers (GMA), whose polymer has low glass transition temperature ( T g ), is important for the formation of wrinkled morphology. The amount of toluene and polydimethylsiloxane also affects the surface morphology of microspheres. In addition, the effect of polydimethylsiloxane is also more significant. The preparation process of the wrinkled P(GMA‐St‐EGDA) microspheres with abundant epoxy groups can be amplified. The morphology of the material prepared in the 100 L reactor is well maintained, and the yield in the size range of 80–160 µm is more than 80%. The surface wrinkled porous polymer microspheres have potential applications in the fields of enzyme carrier, separation and purification, and light scattering. Abstract : In this work, the suspension polymerization method is used for the preparation of porous polymer microspheres with different surface morphology, and the preparation mechanism is systematically expounded. Especially, surface wrinkled porous microspheres are prepared by this method and amplified in a 100 L industrial reactor. The obtained microspheres have potential applications in enzyme carrying, separation and purification, and light scattering.